Inescapable Romance : Studies in the Poetics of a Mode - Parker, Patricia A., 1946- (Book collections on Project MUSE., 1979)
Defining "romance" as a form that simultaneously seeks and postpones a particular end, revelation, or object, Patricia Parker interprets its implications and transformations in the works of four major poets-Ariosto, Spenser, Milton, and Keats. In placing the texts within their literary and historical contexts, Professor Parker provides at once a literary history of romance as genre, a fresh reading of individual poems, and an exploration of the continuing romance of figurative language itself.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.